Expert-Based Narrative Review on Compression UltraSonography (CUS) for Diagnosis and Follow-Up of Deep Venous Thrombosis (DVT) - Mario D’Oria; Laura Girardi; Ahmed Amgad; Mohab Sherif; Gabriele Piffaretti; Barbara Ruaro; Cristiano Calvagna; Philip Dueppers; Sandro Lepidi; Marco Paolo Donadini (Diagnostics)
Deep venous thrombosis (DVT) is a pathological condition that develops when a thrombus forms within the deep venous system. Typically, it involves the lower limbs and, less frequently, the upper extremities or other unusual districts such as cerebral or splanchnic veins. While leg DVT itself is rarely fatal and occasionally can lead to limb-threatening implications, its most fearsome complication, namely pulmonary embolism, is potentially fatal and significantly contributes to increased healthcare costs and impaired quality of life in affected patients and caregivers. Thanks to its high accuracy, ease of use, and safety profile, duplex ultrasound (DUS), particularly compression ultrasound (CUS), has emerged as the first-line imaging modality for DVT diagnosis. The evaluation of suspected DVT needs a multifaceted approach, and in this context, CUS rapidly became a key diagnostic tool owing to its many unique advantages. Its central role in the diagnostic algorithm of suspected DVT is clearly established in the latest clinical practice guidelines from the European Society for Vascular Surgery and the American Society of Haematology. Indeed, DUS effectively visualizes blood flow and identifies abnormalities like clot formation with high sensitivity (typically exceeding 90% for proximal DVT) and specificity (often approaching 100% for proximal DVT). Additionally, CUS is non-invasive, readily available at the bedside, and avoids radiation exposure, resulting in an ideal method for various clinical settings. CUS has been shown to have a substantial role not only in the diagnosis of an acute DVT but also in the follow-up of its management. Moreover, this method can provide a prognostic assessment, mostly in terms of risk stratification for recurrent thrombosis and/or for potential complications, such as post-thrombotic syndrome. In summary, given its established benefits, CUS is a technique that many physicians should be familiar with, especially those working in emergency departments, intensive care units, or general wards. When needed, healthcare operators with more advanced US skills (such as radiologists, angiologists, or vascular surgeons) may be called upon to provide a second look in case of uncertainty and/or need for additional information.